Catálogo liquénico de las calizas de Madrid (España) - Barreno, Eva; Merino, A. (Lazaroa, 1981)
Barreno, E. & Merino, A. Lichenic Catalogue of ¡he limestone in Madrid (Spain). Lararoa, 3: 247-268 (1981). An initial Catalogue of the lichen flora that grows on Pontian limestone rocks between the basins of the Henares and Tajuña rivers (Madrid, Spain) is presented. A total of 101 taxa are recognized, 11 of which are new records for the Spanish flora, with remarks on Iheir ecology and chorology.